STUDI KETERSEDIAAN PRASARANA AIR BERSIH PDAM KOTA GORONTALO - Arfan Utiarahman (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2017)
This research executed in Town Gorontalo Propinsi Gorontalo. Technique in data analysis is analysing is descriptive quantitativeness and statistic analysis method inferensial. For the agenda of evaluation and increasing, done by is secondary data collecting in the form of population, brasque data, amount of water required data, linear circuit map, and also done by primary data collecting through Kuisoner to 151 responder (brasque) concerning grade, kontinuitity and quantity of clean water. Hereinafter analyse magnitude of level of cleanness amount of water required for projection until year 2015 with standar at NSPM Kimpraswil 2002 concerning Device procedures Technique In Drinking Water. Result analysed, condition of cleanness water infrastructure PDAM in this time enough adequate. For planning of increasing of service until year 2015 required addition of clean water infrastructure or processing unit ( IPA) newly because condition of infrastructure in this time fallen short / fulfill for clean amount of water required in the year 2015. While source of standard water from Bone Rivers and Bolango Rivers still water supply can till year 2015.